Culture Front : Representing Jews in Eastern Europe - Safran, Gabriella, 1967-; Nathans, Benjamin (Book collections on Project MUSE., 2008)
Bringing together contributions by historians and literary scholars, Culture Front explores how Jews and their Slavic neighbors produced and consumed imaginative representations of Jewish life in chronicles, plays, novels, poetry, memoirs, museums, and elsewhere.